OP0081 Identification of a Sjögren's Syndrome-Associated Variant that Influences OAS1 Isoform Switching and Protein Expression. (9th June 2015) - Lessard, C.; Li, H.; Ice, J.A.; Adrianto, I.; Montgomery, C.G.; Alevizos, I.; Witte, T.; Rischmueller, M.; Wahren-Herlenius, M.; Omdal, R.; Jonsson, R.; Rhodus, N.L.; et al.
Abstract : Background: Sjögren's syndrome (SS) is a common, autoimmune exocrinopathy characterized by symptoms of dry eyes and mouth present in 0.7% of the European American population. Gene expression profiling (GEP) has previously demonstrated overexpression of transcripts induced by interferons (IFN) in SS patients. Objectives: In this study, we sought to identify and characterize underlying genetic contributions to dysregulation of IFN pathways in SS. Methods: IFN signature genes of interest were selected from GEP studies performed in 115 anti-Ro positive SS cases and 73 controls using microarray data and evaluated for cis -expression quantitative trait loci (eQTL) in 178 subjects by integration with genome-wide association study (GWAS) data. Gene splicing patterns were evaluated using RNA-sequencing (RNA-seq) performed in 57 SS cases and 27 controls on the Illumina platform. Results: GEP showed that OAS1, an IFN-inducible gene involved in inhibition of virus replication, was significantly overexpressed in SS patients. Multiple cis -eQTL were identified in OAS1 with the most significant peaking at rs10774671, strengthening prior evidence of this variant for disease association (( p =8.47×10 -5 ) obtained in our large GWAS dataset consisting of 765 cases and 3825 controls. We further replicated this genetic association in an independent set of 514 cases and 3466 controls followed by meta-analysis ( p =2.59×10 -9 ; OR=0.75). The risk allele "A" of rs10774671 is a splice site consensus variant located at the junction between intron-5 and exon-6 of OAS1, and thus may switch the primary isoform, p46, to various alternatives. Transcripts measured by RNA-seq were reconstructed and the abundance of isoforms was compared across samples according to the genotype of rs10774671. The risk allele "A", which demolishes the splicing consensus sequence, was correlated with higher expression of p42, p48, and p44 isoforms, but a lower expression of the normally spiced OAS1 isoform, p46. Functional characterization of different OAS1 isoforms indicated that the alternatively spliced isoforms resulted in impaired protein expression and lack of response to type I IFNs. Conclusions: We identified OAS1 as a novel candidate SS locus. The risk allele "A" has been reported to result in decreased Oas1 enzyme activity. These results suggest a mechanism in which alternatively spliced OAS1 transcripts lead to reduced viral clearance resulting in perpetuation of type I IFN signaling in SS. Disclosure of Interest: None declared